The moderating influence of perceived competence in learning on mentored students' school performance - Simões, F.; Alarcão, M. (Learning and Individual Differences, 2014)
Our aim is to examine whether mentored students' Perceived Competence in Learning (PCL) moderates school performance outcomes in school-basedmentoring (SBM) programs delivered by teachers. A three-stage longitudinal study was conducted in order to compare mentored (n = 157) and non-mentored students (n = 160) enrolled in formal basic education (5th to 8th grades).Multivariate Analyses of Covariance (MANCOVA) revealed that mentoring was moderately effective in improving mentees' Portuguese grades and Grade Point Average (GPA) and reducing the number of unexcused absences compared to equivalent non-mentored students. The study also demonstrated that the mentees' PCL had a significant moderating effect on improvement in their Math grades. The different patterns of change in PCL during SBM also contributed to a variation in school performance outcomes. These results suggest that SBM delivered by experienced educators may enhance PCL as well as school performance in formal learning contexts.